Talking about Chat at Work in the Global South: An Ethnographic Study of Chat Use in India and Kenya - McGregor, Moira; Bidwell, Nicola J; Sarangapani, Vidya; Appavoo, Jonathan; O'Neill, Jacki (Computer-Human Interaction, 2019)
In this paper, we examine how two chat apps fit into the communication ecosystem of six large distributed enterprises, in India and Kenya. From the perspective of management, these chat apps promised to foster greater communication and awareness between workers in the field, and between fieldworkers and the enterprises administration and management centres. Each organisation had multiple different types of chat groups, characterised by the types of content and interaction patterns they mediate, and the different organisational functions they fulfil. Examining the interplay between chat and existing local practices for coordination, collaboration and knowledge-sharing, we discuss how chat manifests in the distributed workplace and how it fits – or otherwise – alongside the rhythms of both local and remote work. We contribute to understandings of chat apps for workplace communication and provide insights for shaping their ongoing development.